Knowledge, Attitude, and Practice of Self-Medication Among the Population of Balikpapan During COVID – 19 Pandemic - Karuniawati, Hidayah; Tsaniya, Naura Azka; Ismail, Wan Ismahanisa (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Over the past three years, the COVID-19 pandemic has caused significant changes in people's lives. One of the significant changes was the increase in self-medication activities. This study aims to provide an overview of the knowledge, attitudes, and practices among Balikpapan's population in self-medication during the COVID-19 pandemic. A total of 385 respondents were obtained from October 2022 until January 2023. The average value of respondents’s self-medication knowledge was 64.39% ± 21.37, with 28.6% included in the category of having good knowledge, while 37.9% and 33,55% of respondents had moderate and poor knowledge, respectively. The average self-medication attitude score was 74.60% ± 8.69, with most respondents having a neutral attitude towards self-medication (69.6%). In comparison, 38.1% of respondents had a positive attitude, and 2.3% had a negative attitude. The most common symptoms reported for self-medication included flu (22.12%), fever (20.92%), and cough (20.84%). The drugs most used by respondents in self-medication were paracetamol (29.09%), antacids (11.42%), mefenamic acid (4.17%), and cough syrup (3.95%). Inappropriate self-medication practices found that 13.54% of drugs used and 9.23% kept were prescription-only drugs, including antibiotics. Of 48.05% of respondents inappropriately disposed of expired drugs.